2000
DOI: 10.1046/j.1365-3024.2000.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Chagasic patients develop a type 1 immune response to Trypanosoma cruzi trans‐sialidase

Abstract: Infective forms of Trypanosoma cruzi, the parasite that causes Chagas' disease, express on their surface an enzyme denominated trans-sialidase (TS). The present study was designed to evaluate the naturally acquired immune responses to a bacterial recombinant protein representing the catalytic domain of TS in chronically infected chagasic individuals. The cellular immune response was measured by in-vitro T-cell proliferation and by interferon (INF)-gamma, interleukin (IL)-4 and IL-10 production in response to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 17 publications
7
45
0
3
Order By: Relevance
“…These results are consistent with a modulatory type of immune response (Ribeirao et al 2000, Abel et al 2001). Importantly, a recent study demonstrated a biased distribution of high IL-10 expression amongst indeterminate chagasic patients.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with a modulatory type of immune response (Ribeirao et al 2000, Abel et al 2001). Importantly, a recent study demonstrated a biased distribution of high IL-10 expression amongst indeterminate chagasic patients.…”
Section: Discussionsupporting
confidence: 88%
“…These results were confirmed by other studies, which also showed that, although the levels of TNF-α and NO were higher in sera from chagasic patients, compared to non-chagasic individuals, no difference was observed between asymptomatic and symptomatic chagasic patients (Perez-Fuentes et al 2008). IFN-γ levels were similar in the sera of asymptomatic individuals and CARD patients that presented the form of the disease (Ribeirao et al 2000). Thus, the findings of several studies have failed to clearly establish a correlation between the concentration of circulating cytokines and the cardiac form of Chagas disease.…”
supporting
confidence: 87%
“…Although the present results showed no differences between IL-10 and IFN-γ levels in CARD and IND patients, the IND patients displayed a positive correlation between inflammatory and regulatory cytokine production, indicating a controlled immune response. These findings are supported by the higher production of IFN-γ and TNF-α associated with high IL-10 levels described in IND patients, while CARD patients showed an unregulated Th1 response (Bahia-Oliveira et al 1998, Correa-Oliveira et al 1999, Ribeirao et al 2000, Abel et al 2001, Gomes et al 2005. A lack of co-regulation between inflammatory and anti-inflammatory cytokines associated with severe disease was also demonstrated in human patients with leishmaniasis (Gaze et al 2006), strengthening this hypothesis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Mononuclear cells increase their cytokine production, leading to increased plasma levels of TNF-α and IFN-γ, and are even detected in infected individuals with indeterminate forms of Chagas disease (Ribeirão et al 2000, Abel et al 2001, Ferreira et al 2003, Talvani et al 2004, which is probably in response to parasite persistent. The subset of patients that develop Chagas cardiomyopathy displays an array of immunological alterations consistent with an exacerbated Th1 immune response.…”
Section: Cytokines and Chemokines In The Chronic Phase Of T Cruzi Inmentioning
confidence: 99%